2013
DOI: 10.3367/ufne.0183.201308d.0863
|View full text |Cite
|
Sign up to set email alerts
|

Excitation of cyclic Sommerfeld waves and Wood's anomalies in plane wave scattering from a dielectric cylinder at oblique incidence

Abstract: In this paper we consider a process of plane wave scattering from a single dielectric cylinder at oblique incidence under which it is possible to excite long range cyclic Sommerfeld waves (CSWs) and consequently cyclic Sommerfeld resonances (CSRs) of different orders. It is shown that the CSRs are analogous to Wood's anomalies occurred under plane wave scattering from one dimensional (1D) metallic diffraction gratings. The conditions which are necessary for an effective excitation of CSWs and CSRs with high qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0
2

Year Published

2014
2014
2016
2016

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 36 publications
(73 reference statements)
1
15
0
2
Order By: Relevance
“…Yet what do these two scattering processes in the 1D photonic crystals and the cylindrical surface have in common? In the following discussion we will use our results obtained in [8] to try to answer this question. It is known that mathematically the incident and scattering waves under plane wave scattering from a 1D diffraction grating and a cylindrical surface are expressed according to Fourier and Fourier -Bessel expansions.…”
Section: Azimuthal Momentum Of Cylindrical Waves and Excitation Of Womentioning
confidence: 94%
See 4 more Smart Citations
“…Yet what do these two scattering processes in the 1D photonic crystals and the cylindrical surface have in common? In the following discussion we will use our results obtained in [8] to try to answer this question. It is known that mathematically the incident and scattering waves under plane wave scattering from a 1D diffraction grating and a cylindrical surface are expressed according to Fourier and Fourier -Bessel expansions.…”
Section: Azimuthal Momentum Of Cylindrical Waves and Excitation Of Womentioning
confidence: 94%
“…The angle of incidence is θ = 0.02 rad and the refractive index of the capillary and cylinder is n = 1.444. If one calculates the differential backscattering cross section ) 0 ( d σ (ϕ = 0) [8] in the case of the TE polarized incident plane wave: It can be shown that in the case of the plane wave scattering from the dielectric cylinder at oblique incidence it is also possible to observe the anomalies with Lorentzian spectral profiles [8]. As one can see from …”
Section: Azimuthal Momentum Of Cylindrical Waves and Excitation Of Womentioning
confidence: 96%
See 3 more Smart Citations